A peer-assisted learning experience in computer programming language learning and developing computer programming skills - Altintas, Tugba; Gunes, Ali; Sayan, Hamiyet (Innovations in education and teaching international, 2016)
Peer learning or, as commonly expressed, peer-assisted learning (PAL) involves school students who actively assist others to learn and in turn benefit from an effective learning environment. This research was designed to support students in becoming more autonomous in their learning, help them enhance their confidence level in tackling computer programming problems as well as to encourage them towards team work and collective effort. The main purpose of this research is to test the effectiveness of PAL on the C programming language course in the second semester of undergraduate level. For this purpose, an experiment group (peer students) and a control group were statistically compared in terms of midterm and final exam scores and the results showed that peer students were more successful in C programming language.